Commodities of care : the business of HIV testing in China - Fan, Elsa L. (Minneapolis, MN : University of Minnesota Press, 2021)
"How global health practices can end up reorganizing practices of care for the people and communities they seek to serve"--
The productivity of HIV testing -- Making up (and making available) MSM in China -- Markets of and marketing to MSM -- Remaking communities of belonging -- Living with HIV as MSM in China.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 25, 2022).
JSTOR
Keywords: HIV infections -- Prevention -- Economic aspects -- China; AIDS (Disease) -- Prevention -- Economic aspects -- China; Gay men -- Health and hygiene -- China; Gay men -- China -- Social conditions; HIV infections -- Diagnosis -- China; AIDS (Disease) -- Diagnosis -- China; Medical economics -- China; Public health -- China; Infections à VIH -- Prévention -- Aspect économique -- Chine; Sida -- Prévention -- Aspect économique -- Chine; Homosexuels masculins -- Santé et hygiène -- Chine; Homosexuels masculins -- Chine -- Conditions sociales; Économie de la santé -- Chine; Santé publique -- Chine; SOCIAL SCIENCE / Gay Studies; AIDS (Disease) -- Diagnosis; Gay men -- Health and hygiene; Gay men -- Social conditions; HIV infections -- Diagnosis; Medical economics; Public health; China